2013
DOI: 10.1017/s0261143013000032
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect sound forever: loudness wars, listening formations and the history of sound reproduction

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 24 publications
1
19
0
5
Order By: Relevance
“…The current results show that popular music has been getting louder, more compressed, and more bass-heavy. While increases in loudness and compression in music recordings are well known (e.g., Devine, 2013;Oehler et al, 2015;Serrà et al, 2012;Vickers, 2010), far less attention has been devoted to differences across the frequency spectrum. We observed that during the last The evolution of recorded music partly mirrors evolution of technology.…”
Section: Discussionmentioning
confidence: 99%
“…The current results show that popular music has been getting louder, more compressed, and more bass-heavy. While increases in loudness and compression in music recordings are well known (e.g., Devine, 2013;Oehler et al, 2015;Serrà et al, 2012;Vickers, 2010), far less attention has been devoted to differences across the frequency spectrum. We observed that during the last The evolution of recorded music partly mirrors evolution of technology.…”
Section: Discussionmentioning
confidence: 99%
“…As has been shown by Devine (2013), loudness wars did not begin in the 1980s, rather they had been present at the turn of the nineteenth and twentieth centuries at the beginning of electronic sound amplification. The result-if sound quality is defined by the detailedness, life-likeness, and undistortedness of the sound-was serious damage, distortion, and radical simplification of the sound in every case.…”
Section: Values Meanings Ethics: Cultural Factors In the Formation mentioning
confidence: 96%
“…Certain genres such as heavy metal or dance music demand more loudness than other more dynamic ones: jazz or classical. Since the loudness of a master depends upon comparison to other recordings a result is the 'loudness wars' wherein there is competitive pressure for audio mastering engineers to achieve loudness at the expense of dynamic range and clarity to attract and satisfy clients (Devine, 2013).…”
Section: The Creative Industry Of Audio Masteringmentioning
confidence: 99%